2008
DOI: 10.1007/s10926-008-9156-x
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehensive Muscular Activity Profile (CMAP): Its High Sensitivity, Specificity and Overall Classification Rate for Detecting Submaximal Effort on Functional Capacity Testing

Abstract: Introduction. A traditional problem faced by clinicians attempting to objectively measure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Together with the earlier reviewed investigations by Gatchel and colleagues (Gatchel, Ricard, Choski, et al., 2009 and Gatchel and Theodore 2009), these results further attest to the clinical utility of the CMAP, which is a safe, non‐invasive, and objective measure of muscle functioning/impairment, as well as subject effort during the measurement process. Such findings have significant clinical implications for physical impairment evaluations.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Together with the earlier reviewed investigations by Gatchel and colleagues (Gatchel, Ricard, Choski, et al., 2009 and Gatchel and Theodore 2009), these results further attest to the clinical utility of the CMAP, which is a safe, non‐invasive, and objective measure of muscle functioning/impairment, as well as subject effort during the measurement process. Such findings have significant clinical implications for physical impairment evaluations.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, in the earlier study by Gatchel et al. (Gatchel, Ricard, Choski, et al., 2009), it was found that effort could be affected by “secondary gain‐type” instructions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A recent randomized controlled study was conducted to assess the ability of the CMAP to accurately determine whether maximal effort was put forth by individuals (Gatchel et al 2008). Within this study, participants undergoing rangeof-motion and lifting capacity assessments were asked to either give maximal effort or submaximal effort on each task.…”
Section: The Comprehensive Muscular Activity Profilementioning
confidence: 99%